2021
DOI: 10.3389/frwa.2021.729722
|View full text |Cite
|
Sign up to set email alerts
|

The Five Ws of the Water-Energy-Food Nexus: A Reflexive Approach to Enable the Production of Actionable Knowledge

Abstract: The water-energy-food nexus is now a popular approach in the sustainability field. However, whereas the nexus calls for more holistic, inter- and transdisciplinary approaches, the research produced over the past decade has been fragmented and specialized. Furthermore, there is still a gap between the nexus as a descriptive and analytical concept and its operationalization. Nexus research needs a shift from “thinking” to “action,” which we understand as the production of actionable knowledge. This paper delves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…However, this brings along the risk of overlooking local characteristics and specific needs, such as typical production and consumption patterns and possible related environmental impacts (Arthur et al 2019 ). Our research showed how local characteristics and specific needs can be taken into account through active collaboration with local stakeholders and, in doing so, enhance the saliency and legitimacy of the knowledge produced (Dalla Fontana et al 2021 ).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, this brings along the risk of overlooking local characteristics and specific needs, such as typical production and consumption patterns and possible related environmental impacts (Arthur et al 2019 ). Our research showed how local characteristics and specific needs can be taken into account through active collaboration with local stakeholders and, in doing so, enhance the saliency and legitimacy of the knowledge produced (Dalla Fontana et al 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…The process of engagement was mainly between academics and practitioners. However, we recognize that a greater involvement of local communities (Dalla Fontana et al 2021 ), and in particular of local farmers in our case, would have been valuable to bring different insights. This was also reported as one of the flaws of this project by the representatives of the municipality and the LoP project.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Within this framework, the EU’s Horizon 2020 Programme funded several projects to investigate the strong relationship amongst the water, energy, and food subsystems (WEF Nexus), in relation to the climate change impacts, as being essential mechanisms in achieving the goals of the European Green Deal. This deal aims to make the EU’s economy sustainable by making the WEF Nexus an effective tool in sustainable development, and by turning climate and environmental challenges into opportunities in all policy areas Fontana et al ( 2021 ) Frontiers in Water Presented “Five W Questions” (FWQ) as an iterative guide to the concept of WEF Nexus to encourage reflexivity and interdisciplinary dialogue, while aiming to produce actionable knowledge. The FWQ are: (i) ‘why’, in which the purpose of correlative research for actionable knowledge can be explored; (ii) ‘what’, in which the physical aspect of the interdependence and interactions amongst water, energy, and food subsystems (WEF Nexus) can be understood; (iii) ‘where’, in which issues of scale, interactions between scales, and the geographic context of the WEF Nexus or interdependence can be discussed; (iv) ‘when’, in which the temporal dimensions of interconnected research with a particular focus on intergenerational trade-offs can be considered; and (v) ‘who’ which focuses on relevant stakeholders and the importance of understanding justice and equity issues Heal et al ( 2021 ) Hydrological Science Journal Pointed out that the role of water quality and, in particular, its impact on health, the environment, and the broader well-being of the water–energy–food (WEF) Nexus, is rarely acknowledged.…”
Section: Introductionmentioning
confidence: 99%